A Case Study of Female Adult Learners in Community Colleges: Understanding Multiple Role Navigation - Tara J. Thompson; Susan J. Barcinas (Adult Education Research Conference, 2014)
This qualitative case study focused upon better understanding and analyzing how female mothers and adult learners in community colleges perceived and navigated multiple roles.